Art of our time : Ten Years of the Praemium Imperiale. - Adair, Gilbert; Frampton, Kenneth; Hugill, Andrew; Lucie-Smith, Edward; Lynton, Norbert; Miyoshi, Akira; Restany, Pierre; Varnedoe, Kirk (Tokyo : The Japan Art Association, 1999)
Ando, Tadao ; Attenborough, Richard ; Aulenti, Gae ; Balthus ; Béjart, Maurice ; Bergman, Ingmar ; Berio, Luciano ; Bernstein, Leonard ; Bill, Max ; Boulez, Pierre ; Brook, Peter ; Carné, Marcel ; Caro, Anthony ; César ; Chillida, Eduardo ; Christo & Jeanne-Claude ; Correa, Charles ; Dutilleux, Henri ; Fellini, Federico ; Gielgud, John ; Gubaidulina, Sofia ; Hockney, David ; Johns, Jasper ; Karavan, Dani ; de Kooning, Willem ; Kurosawa, Akira ; Ligeti, György ; Mastroianni, Umberto ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Meier, Richard ; O'Gehry, Frank ; Pei, I.M. ; Piano, Renzo ; Pomodoro, Arnaldo ; Rauschenberg, Robert ; Richter, Gerhard ; Rostropovich, Mstislav ; Schnittke, Alfred ; Segal, George ; Serra, Richard ; Shankar, Ravi ; Siza, Alvaro ; Soulages, Pierre ; Stirling, James ; Tange, Kenzo ; Tàpies, Antoni ; Twombly, Cy ; Utaemon, Nakamura ; Wajda, Andrzej ; Webber, Andrew Lloyd ; Zao Wou-Ki
English-French-German-Italian-Japanese
boek